Neurologic Music Therapy Improves Participation in Children With Severe Cerebral Palsy - Santonja-Medina, Clara Susana; Marrades-Caballero, Eugenio; Santonja-Medina, Fernando; Sanz-Mengibar, Jose Manuel (Frontiers in Neurology, 2022)
Positive effects after neurologic music therapy (NMT) have been described regarding the motor function of children with severe cerebral palsy (CP). This study aimed to quantify improvements in participation, as well as complexity on task-related manual activities in children with severe bilateral CP. This analytic quasi-experimental study exposed 17 children with severe cerebral palsy to 13 NMT sessions to improve motor learning through therapeutic instrumental music performance (TIMP), using principally percussion musical instruments. Hoisan software video recording was used to quantify participation involved in creating music. In addition, the number of active movements performed in each NMT session was quantified. Significant improvements were found in the participation variables “visual contact”, “motor participation” and “motor participation repetitions”. Significant differences were also found in the subcategory “reaching and stroke”, “hitting with the hand” and “grasping and hitting”. The use of therapeutic of TIMP in children with severe CP improves participation during manual activities utilising percussion instruments, therefore increasing the intensity of the psychomotor intervention.